ผลของการจัดรูปแบบบริการพยาบาลผ่าตัดที่เน้นการดูแลครอบครัวต่อความวิตกกังวลของผู้ป่วยและครอบครัวและความพึงพอใจของพยาบาล - เพียรจิตต์ ภูมิสิริกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purposes of this quasi experimental research were to study the effects of perioperative nursing service management model emphasizing caring for family on anxiety of patients and families, and nurses satisfaction. The research subjects consisted of 40 surgical patients, 40 family members and 10 professional nurses working in preoperating unit, operating room and post anesthetic care unit, Ramathibodi Hospital. The patients and their families were randomly assigned to experimental group and control group by matched pair technique. Research instruments were a perioperative nursing service management model emphasizing caring for family training project, lesson plan of perioperative nursing service management model emphasizing caring for family, handbook of perioperative nursing service practice, patient and family self-care instruction video, patient and family booklet and a questionnaire to evaluate perioperative nursing service management model. Research data were obtained by questionnaires of patients anxiety, families anxiety, and nurses satisfaction. The instruments were validated by panel of experts. The Cronbach s alpha coefficient of the questionnaires were .89, .92, and .91 respectively. Statistical techniques used in data analysis were percentage, mean, standard deviation, t-test and Wilcoxon matched- pairs signed ranks test. Majors results were as follows: 1. The patients anxiety in the experimental group was significantly lower than that of the control group at the .05 level. 2. The families anxiety in the experimental group was significantly lower than that of the control group at the .05 level. 3. The overall nurses satisfaction after using perioperative nursing service management model emphasizing caring for family was significantly higher than before at the .05 level. The implementation of perioperative nursing service management model emphasizing caring for family would help in reducing both patients and families anxiety. The perioperative nurses could also exhibit their professionalindependent role. This, intern, could enhance good relationship with the patients and families as well as reflected the quality of perioperative nursing care.